Discussion of An Assessment of Laboratory Experiments in Accounting - Hogarth, Robin M. (Journal of Accounting Research, 1982)
Robin M. Hogarth, Discussion of An Assessment of Laboratory Experiments in Accounting, Journal of Accounting Research, Vol. 20, Supplement: Studies on Current Research Methodologies in Accounting: A Critical Evaluation (1982), pp. 108-116